"Planning and nuisance: revisiting the balance of public v private interest in land use development" - Victoria Jenkins (Journal of Environmental Law, 2011)
This article considers the balance of public and private interests in land use planning; in particular, we seek to explore the nuisance/planning interface in light of two relatively recent developments in England and Wales, namely the Court of Appeal decision in Watson v Croft Promo-Sport and the enactment of the Planning Act 2008. Thus, it is believed timely to reconsider the continuing role of private nuisance in the legal control of land use development. We argue that, given that the Planning Act 2008 effectively excludes an action in nuisance in the case of nationally significant infrastructure projects, little room is now left for the courts to be involved in deciding those cases in which planning permission might abrogate private interests. However, where the courts are called upon to do so, we argue that they should focus on their traditional role in invoking the locality doctrine to judge whether the use of land is reasonable rather than involve themselves in questions of the ‘public interest’ nature of the development. It is further argued that in the residual cases where the courts consider nuisance in the context of development authorised by planning consent, private law is able to operate as an indirect means of challenging the outcome of the planning process but, given the democratic legitimacy (albeit imperfect) of the planning regime, the courts ought to adopt a more flexible approach to the question of the appropriate remedy.